Penanaman Nilai-nilai Toleransi Beragama pada Pembelajaran Pendidikan Agama Islam (PAI) - Zulyadain Zulyadain (Al-Riwayah : Jurnal Kependidikan, 2018)
Being tolerant is allowing others to be themselves, respecting others, respecting their origin and background. Tolerance invites dialogue to communicate the existence of mutual recognition. This is the picture of tolerance in its solid form. This article aims to find out the cultivation of religious tolerance values in the learning of Islamic Education (PAI). The results of the study indicate that the following measures are: first, schools should establish and implement local laws, for example school laws that are specifically applied in a particular school. Second, to build a sense of understanding from an early age between students who have different religious beliefs, the school must play an active role in promoting religious dialogue or interfaith dialogue which must remain in the guidance of teachers in the school. Third, another importantthing in the application of the education of tolerance, the curriculum and textbooks used and applied in schools. Furthermore, the teaching model that can be an option for the cultivation of religious tolerance values in schools includes communicative teaching models and active teaching models.